Implementasi Pembelajaran Kooperatif dalam Meningkatkan Hasil Belajar Matematika Dasar Menggunakan Aplikasi Minitab Versi 8 - Qurniati, Nofi; Elfianty, Lena (LPPM UNIKA Santo Thomas Medan, 2019)
The purpose of this study was to determine the effect of the cooperative Technique of sending question with computer media is Minitab Application in improving learning outcomes. This research method is a experimental method. This research was conducted in state Angkasa Junior High school of Padang at the event semester of the 2018/2019 academic year. The sample of this study was class VII1 and VII3 as the control class. The average value of student understanding of learning outcomes by cooperative Technique of sending question with computer media is 62,55, while the conventional learning model is 54,98, value thitung= 3,40 and t tabel = 1,67.